Distinctive laterality of neural networks supporting action understanding in left- and right-handed individuals: An EEG coherence study. (August 2015) - Kelly, Rachel; Mizelle, J.C.; Wheaton, Lewis A.
Abstract: Prior work has demonstrated that perspective and handedness of observed actions can affect action understanding differently in right and left-handed persons, suggesting potential differences in the neural networks underlying action understanding between right and left-handed individuals. We sought to evaluate potential differences in these neural networks using electroencephalography (EEG). Right- and left-handed participants observed images of tool-use actions from egocentric and allocentric perspectives, with right- and left-handed actors performing the actions. Participants judged the outcome of the observed actions, and response accuracy and latency were recorded. Behaviorally, the highest accuracy and shortest latency was found in the egocentric perspective for right- and left-handed observers. Handedness of subject showed an effect on accuracy and latency also, where right-handed observers were faster to respond than left-handed observers, but on average were less accurate. Mu band (8–10 Hz) cortico-cortical coherence analysis indicated that right-handed observers have coherence in the motor dominant left parietal-premotor networks when looking at an egocentric right or allocentric left hands. When looking in an egocentric perspective at a left hand or allocentric right hand, coherence was lateralized to right parietal-premotor areas. In left-handed observers, bilateral parietal-premotor coherence patterns were observed regardless of actor handedness. These findings suggest that the cortical networks involved in understanding action outcomes are dependent on hand dominance, and notably right handed participants seem to utilize motor systems based on the limb seen performing the action. The decreased accuracy for right-handed participants on allocentric images could be due to asymmetrical lateralization of encoding action and motoric dominance, which may interfere with translating allocentric limb action outcomes. Further neurophysiological studies will determine the specific processes of how left- and right-handed participants understand actions. Highlights: There are behavioral benefits of seeing actions in an egocentric perspective. We evaluated hemispheric laterality of neural networks when viewing action images. Right-handed participants showed lateralized coherence patterns. Left-handed individuals show a bilateral coherence pattern.